Patient Factors Associated with Complementary and Alternative Medicine Use Among Cancer Patients at a County Referral Hospital, Kenya - Etole, Bravin G.; Oluchina, Sherry; Mbithi, Wambua (African Journal of Health Sciences Volume 36, Issue No.5, September – October 2023, 2023)
BACKGROUND Despite numerous global reports on the use of complementary and alternative medicine (CAM), no studies have been published regarding its use at Machakos Level 5 Hospital. Therefore, this study aims to identify patient-related factors associated with CAM use among cancer patients at this Level 5 hospital in Kenya. METHODOLOGY A mixed method, cross-sectional design was implemented at Machakos level five hospital in Kenya. A Census was carried out, using a face-to-face researcher-administered questionnaire among 80 cancer patients receiving treatment at the clinic. Critically ill and mentally unstable patients were excluded. A Chi-square test assessed variable associations, considering p < 0.05 as statistically significant. Logistic regression analyzed variable relationships. RESULTS Gender was significantly associated with CAM use (p=0.014). Regression analysis revealed that Male patients were 79% less likely to use CAM (OR=0.21, 95% CI 0.042-1.003, p=0.050). Patients who had received radiotherapy were likely to use CAM (p=0.032), however, on regression analysis there was no significant association. Believes that CAM improves health (χ 2=9.231, p-0.010), supports conventional treatment (χ 2=15.620, p-0.001), cures cancer (χ 2=12.661, p-0.002), manages treatment side effects (χ 2=11.045, p-0.004), relieves cancer symptoms (χ 2=9.008, p-0.011), promotes self-healing (χ 2=16.969, p-0.001), and gives hope (χ 2=17.512, p-0.001) were significantly associated with CAM use. CONCLUSION AND RECOMMENDATION There was a significant association between patient characteristics and CAM use among cancer patients. Improving patient-healthcare worker communication could encourage reporting of CAM usage. Further research is needed to explore the efficacy, safety, and tolerability of CAM in cancer patients.
Keywords: Complementary Medicines; Alternative Medicines; Alternative Therapy